2017
DOI: 10.1590/1678-457x.24816
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of lasagnas with dried mix of tuna and tilapia

Abstract: The aim of this study was to develop a lasagna pasta enriched with dried mix of tuna (30%) and tilapia (70%) and formulate ready lasagna with enriched pasta. Lasagna pasta was elaborated with increasing levels (0, 5, 10 and 15%) of dried mix. Moisture, lipids and calories were not different between the inclusion levels; crude protein and ash increased linearly, carbohydrates reduced linearly, according to increasing levels of inclusion. There was an increase in n-3 and n-6 fatty acids with the inclusion of mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
8
0
4
Order By: Relevance
“…Furthermore, there were no remarkable changes in texture and appearance attributes due to the low percentage of fish concentrate added (3%). Regarding the above, earlier research that used tuna and tilapia mill meat to making laminated pasta (lasagnas) demonstrated there were no significant differences in these aspects either [41]. According to Figures 3 and 4, sea bass had an intermediate profile between control pasta and tuna pasta.…”
Section: Sensory Analysismentioning
confidence: 79%
“…Furthermore, there were no remarkable changes in texture and appearance attributes due to the low percentage of fish concentrate added (3%). Regarding the above, earlier research that used tuna and tilapia mill meat to making laminated pasta (lasagnas) demonstrated there were no significant differences in these aspects either [41]. According to Figures 3 and 4, sea bass had an intermediate profile between control pasta and tuna pasta.…”
Section: Sensory Analysismentioning
confidence: 79%
“…The lower caloric value is a consequence of the reduction of carbohydrates and lipids and the increase in the protein content, which resulted in better nutritional value of the pizzas dough with inclusion of dehydrated mix of tilapia and salmon. The decrease in the caloric value of the food through the inclusion of fish mix was also observed for other food products, such as lasagna (Kimura et al, 2017), pasta (Goes et al, 2016), extruded snacks (Justen et al, 2017) and onion sticks (Coradini et al, 2015).…”
Section: Characterization Of the Pizza Dough Samples With Inclusion Of Dehydrated Tilapia And Salmon MIXmentioning
confidence: 60%
“…Considering these facts the incorporation of fish nutrients into ready-to-eat products can be effective to increase the protein content, fatty acid profile and mineral composition of these foods (Campelo et al, 2017;Kimura et al, 2017). The health benefits of fish consumption are mainly due to the high quality protein content, vitamins and other essential nutrients (Domingo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All analyzes of attributes presented means above acceptability of 5, which refers to the indifferent concept according to Dutcosky (2015). Angelini et al (2013); Fogaça et al (2015); Vieira et al (2015); Kimura et al (2017) worked with restructured products using tilapia MSM and also obtained good product acceptance.…”
Section: Sensory Analysismentioning
confidence: 99%